ESR1 polymorphism (rs2234693) influences femoral bone mass in patients with Turner syndrome. Issue 11 (November 2019) - Scalco, Renata C; Trarbach, Ericka B; Albuquerque, Edoarda V A; Homma, Thais K; Inoue-Lima, Thais H; Nishi, Mirian Y; Mendonca, Berenice B; Jorge, Alexander A L
Abstract : Most patients with Turner syndrome (TS) need hormone replacement therapy because of hypergonadotropic hypogonadism; individual outcomes, however, are highly variable. Our objective was to assess the influence of five estrogen receptor 1 gene ( ESR1 ) polymorphisms (rs543650, rs1038304, rs2046210, rs2234693 and rs9340799) on adult height, breast development, uterine volume and bone mineral density (BMD). We studied 91 TS patients from a tertiary hospital using adult estrogen dose. In our group, ESR1 rs2234693 was associated with femoral neck and total hip BMD, and it accounted for around 10% of BMD variability in both sites ( P < 0.01). Patients homozygous for C allele in this polymorphism had significantly lower femoral neck BMD (0.699 ± 0.065 g/cm 2 vs 0.822 ± 0.113 g/cm 2, P = 0.008) and total hip BMD (0.777 ± 0.118 g/cm 2 vs 0.903 ± 0.098 g/cm 2, P = 0.009) than patients homozygous for T allele. The other four ESR1 polymorphisms were not able to predict any of the above estrogen therapy outcomes in an isolated manner. Patients homozygous for the haplotype GCG formed by polymorphisms rs543650, rs2234693 and rs9340799 had an even more significantly lower femoral neck BMD (0.666 ± 0.049 vs 0.820 ± 0.105 g/cm 2, P = 0.0047) and total hip BMD (0.752 ± 0.093 vs 0.908 ± 0.097 g/cm 2, P  = 0.0029) than patients homozygous for haplotypes with a T allele in rs2234693. In conclusion, homozygosity for C allele in ESR1 rs2234693 and/or for GCG haplotype appears to be associated with lower femoral neck and total hip BMD. We believe that the identification of polymorphisms related to estrogen outcomes may contribute to individualization of treatment in TS.